Analisis al-ḥarakāt (vokal): kajian ilmu aswat dalam ceramah syaikh dr. Malik husain sya’ban hidup untuk apa? - Rahma, Sri Rahmawati Baso (Maliki Interdisciplinary Journal, 2026)
This study discusses Al-Ḥarakāt (vowels) from the perspective of Arabic phonetics and analyzes their realization in Sheikh Dr. Malik Husain Sha’ban’s lecture entitled “What is the Purpose of Life?” at 01:47–02:04. The theoretical study covers the definition of Al-Ḥarakāt, the articulation mechanism of vowels, the division of short and long vowels, vowel quality (thin and thick), and their differences from consonants (Aṣ-Ṣawāmit). Phonetic analysis of the lecture shows that the Sheikh pronounces vowels with phonetic characteristics that comply with the rules of Aṣwāt: an open articulation path without obstruction, a difference in duration between short and long vowels, and variations in vowel quality (muraqqaqah/mufakhamah) influenced by the nature of the preceding consonant. These findings reinforce the theory that Arabic vowels exhibit consistent characteristics in terms of articulation, duration, and sound quality, and demonstrate the practical application of Arabic phonetics in the speech of a fluent speaker.